Evidence‐Practice Gaps in Postdischarge Initiation With Oral Anticoagulants in Patients With Atrial Fibrillation - Andrea L. Schaffer; Michael O. Falster; David Brieger; Louisa R. Jorm; Andrew Wilson; Melanie Hay; Kira Leeb; Sallie Pearson; Arthur Nasis (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2019)
Background Oral anticoagulant (OAC) therapy reduces the risk of stroke in people with atrial fibrillation (AF), and is considered best practice; however, there is little Australian evidence around the uptake of OACs in this population. Methods and Results We used linked hospital admissions, pharmaceutical dispensing claims, medical services, and mortality data for people in Australia's 2 most populous states (July 2010 to June 2015). Among OAC‐naïve people hospitalized with AF, we estimated initiation of OAC therapy within 30 days of discharge, and persistence with therapy in the first year. We analyzed both outcomes using multivariable Cox regression. In 71 184 people with AF (median age 78 years, 49% female), 22.7% initiated OAC therapy. Initiation was lowest in July to December 2011 (17.0%) and highest in July to December 2014 (30.1%) after subsidy of the direct OACs. In adjusted analyses, initiation was most likely in people with a CHA2DS2‐VA score ≥7 (versus 0) (hazard ratio=6.25, 95% CI 5.08–7.69), and a history of venous thromboembolism (hazard ratio=2.65, 95% CI 2.49–2.83). Of the people who initiated OAC therapy, 39.9% discontinued within 1 year; a lower risk of discontinuation was associated with a CHA2DS2‐VA score ≥7 (versus 0) (hazard ratio=0.22, 95% CI 0.14–0.35), or initiation on a direct OAC (versus warfarin) (hazard ratio=0.55, 95% CI 0.50–0.60). Conclusions We found that OAC therapy was severely underutilized in people hospitalized with AF, even among high‐risk individuals. Reasons for this underuse, whether patient, prescriber, or hospital related, should be identified and addressed to reduce stroke‐related morbidity and mortality in people with AF.